2019
DOI: 10.1200/jop.18.00708
|View full text |Cite
|
Sign up to set email alerts
|

Germline BRCA1 Deletion as Driver Mutation for Metastatic Urachal Adenocarcinoma in Patient Who Achieved Complete Response to Rucaparib

Abstract: FIG 1. Hematoxylin and eosin staining of the biopsy specimen from the bladder mass, shown in low (left panel) and high (right panel) magnification. The arrow in the left panel indicates the area highlighted in the right panel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…Most of the included studies were case reports and retrospective case series. The response to EGFR inhibitors, PARP inhibitors, MEK inhibitors and immune checkpoint inhibitors has already been described in eight previous reports (Goss et al, 2005;Testa et al, 2014;Loh et al, 2016a;Collazo-Lorduy et al, 2016;Kardos et al, 2017;Seto et al, 2019;Yonemori et al, 2021)…”
Section: Overall Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Most of the included studies were case reports and retrospective case series. The response to EGFR inhibitors, PARP inhibitors, MEK inhibitors and immune checkpoint inhibitors has already been described in eight previous reports (Goss et al, 2005;Testa et al, 2014;Loh et al, 2016a;Collazo-Lorduy et al, 2016;Kardos et al, 2017;Seto et al, 2019;Yonemori et al, 2021)…”
Section: Overall Resultsmentioning
confidence: 81%
“…Notably, some institutions have investigated the efficacy of agents targeted to the BRCA gene. Seto et al (2019) reported the successful use of rucaparib, a PARP inhibitor, in a patient with metastatic UrC who possessed a germline BRCA1 mutation, thus suggesting that patients with BRCA mutations might be candidates for the use of PARP inhibitors. In a phase I dose escalation study, a UrC patient receiving niraparib was reported to experience disease progression during therapy; however, the BRCA status of patients with UrC was not clarified ( Yonemori et al, 2021 ).…”
Section: Evidence Synthesismentioning
confidence: 99%